Dataset for the establishment of an age model of marine sediment core KH19-6 Leg.4 PC10/MC14 collected from the Agulhas Ridge in the South Atlantic Ocean - Kaoru Kubota; Rosaaideihn Tanabe; Minoru Ikehara; Yukiko Kozaka; Koji Seike; Yosuke Miyairi; Yusuke Yokoyama (Data in Brief, 2023)
A precise age model of marine sediment core is crucial for environmental studies of the past such as paleoceanography, paleoclimatology, and paleo-hazard studies. Here the geochemical dataset is described that is used to determine the age model of marine sediment cores collected from Agulhas Ridge in the South Atlantic Ocean using piston coring and multiple-coring systems during the 30th Anniversary expeditions of R/V Hakuho Maru in 2019–2020 (KH19-6 Leg.4 PC10/MC14, water depth of 4,604 m). The top 3.27 meter of 12.28-meter-long piston core (PC10) and a whole 0.29-m-long multiple core (MC14) were dated. The dataset includes radiocarbon ages of planktonic foraminifera shells and oxygen isotopes of both planktonic (Globigerinoides bulloides, Globorotalia inflata) and benthic (Gyroidina soldanii) foraminifera shells. The top 7.5 kyr record was lost, the ages of 3.27 m depth below sea floor was ∼140 kyr ago, and sedimentation rates were 0.9–5.5 kyr/cm.